Social Characteristics Of Speech Of Characters In Dramatic Works (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
It is known that not every dialogue can create a dramatic work, but a dramatic dialogue is recognized for a play, which embodies the living image of characters, and can create action, not just any action, but a life-dramatic action consisting of a world of conflicts.